Preparation method of dehumidifying antistatic cotton fiber quilt core material
By layering the fibers treated with nano-alumina, silk fibroin and titanium dioxide in the cotton fiber core material, a unidirectional charge conduction and moisture conduction structure is formed, and the problem of insufficient moisture removal and antistatic properties of the cotton fiber core material in the prior art is solved, and better moisture emission and electrostatic elimination effects are achieved.
Patent Information
- Application Number
- CN202510396960.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-04-01
- Publication Date
- 2025-04-29
AI Technical Summary
The existing cotton fiber quilt core materials have weak moisture removal and antistatic properties during use, resulting in moisture and static accumulation of quilts, affecting sleep quality.
By stacking the regenerated cellulose fibers treated with nano-alumina powder and silk fibroin powder, the cotton fibers treated with hydrogen peroxide and the polylactic fibers treated with titanium dioxide in sequence from bottom to top, a unidirectional charge conduction structure and a unidirectional wet structure are formed to improve the moisture-exhaustness and anti-static properties of the core material.
Effective transmission of charge and moisture in the core material and elimination of static electricity, promote water evaporation through photocatalysis, significantly improving the moisture removal and anti-static properties of the material.
Smart Images

Figure CN119900127A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of textile material modification, in particular to the technical field of fiber processing, and in particular to a method for preparing a dehumidifying and antistatic cotton fiber quilt core material. Background Art
[0002] A quilt core is a bedding product primarily used for warmth, consisting of a quilt cover and a filling sewn together in a suitable manner. As consumers' attention to textile quality and sustainability grows, the quilt core material industry is continuously pursuing technological innovation and green development. Quilt core materials include a wide variety of products, including down, wool, cotton, and synthetic fiber quilts. The design philosophy of these products has also evolved from simply providing warmth to prioritizing comfort.
[0003] Cotton fibers have good hygroscopicity, absorbing sweat from the human body and keeping the quilt dry. However, if the humidity of the cotton increases and the surrounding temperature is not high, the moisture contained in the fibers is not easy to evaporate, causing the quilt to become damp. During use, cotton fibers will produce friction and contact with other fibers and the human body, leading to the transfer and accumulation of charge, thus generating static electricity, which affects sleep quality.
[0004] Therefore, it is necessary to improve the preparation method of the quilt core material in the prior art to solve the above problems. Summary of the Invention
[0005] The present invention overcomes the deficiencies of the prior art and provides a method for preparing a dehumidifying and antistatic cotton fiber quilt core material, aiming to solve the defects of the prior art cotton fiber quilt core material in terms of weak moisture removal and antistatic properties during use.
[0006] To achieve the above object, the technical solution adopted by the present invention is: a method for preparing a dehumidifying and antistatic cotton fiber quilt core material, comprising the following steps: S1: adding nano-alumina powder and silk fibroin powder to dimethyl sulfoxide, stirring to obtain a silk fibroin treatment agent, and spraying the silk fibroin treatment agent onto regenerated cellulose fibers for 1-2 hours to obtain modified regenerated cellulose fibers; S2: treating the cotton fiber with a hydrogen peroxide solution for 0.5-1 h to obtain modified cotton fiber; S3: adding nano-titanium dioxide particles to ethanol and stirring to obtain a titanium dioxide treatment agent, and immersing the polylactic acid fiber in the titanium dioxide treatment agent for 30-45 minutes to obtain a modified polylactic acid fiber; S4: Combing and layering the modified regenerated cellulose fiber in S1, the modified cotton fiber in S2, and the modified polylactic acid fiber in S3, wherein the modified regenerated cellulose fiber, the modified cotton fiber, and the modified polylactic acid fiber are arranged from bottom to top to obtain a dehumidifying and antistatic cotton fiber quilt core material.
[0007] In a preferred embodiment of the present invention, the particle diameter of the aluminum oxide powder in S1 is 10-50 nm, the particle diameter of the silk fibroin powder is 200-400 nm, and the mass ratio between the aluminum oxide powder and the silk fibroin powder is 1:5-7.
[0008] In a preferred embodiment of the present invention, the concentration of the silk fibroin powder in the silk fibroin treating agent in S1 is 10-20%, the fineness of the regenerated cellulose fiber is 4-6D, and the regenerated cellulose fiber is one of lyocell fiber, viscose fiber and modal fiber.
[0009] In a preferred embodiment of the present invention, the regenerated cellulose fibers are sprayed in groups during the atomization spraying process in S1, the silk fibroin treatment agent in each group is consistent, and the grouping is based on the atomization spraying time of the silk fibroin treatment agent.
[0010] In a preferred embodiment of the present invention, the spraying time of the regenerated cellulose fibers in several groups is increased from 1 hour to 2 hours, the spraying time difference between several groups is equal, and the spraying time difference is inversely proportional to the number of groups. The number of groups is 6-8 groups. During the layered laying process, the modified regenerated cellulose fibers in each layer are all from the same group, and the spraying time of the modified regenerated cellulose fibers gradually increases from top to bottom.
[0011] In a preferred embodiment of the present invention, the concentration of the hydrogen peroxide solution in S2 is 25-35%, and the fineness of the cotton fiber is 1-2D.
[0012] In a preferred embodiment of the present invention, the ethanol concentration in S3 is 95%, the particle diameter of the nano-titanium dioxide particles is 100-200 nm, and the concentration of the nano-titanium dioxide particles in the titanium dioxide treating agent is 1:10-15.
[0013] In a preferred embodiment of the present invention, the fineness of the polylactic acid fiber in S3 is 1-3D, and the polylactic acid is plasma treated.
[0014] In a preferred embodiment of the present invention, the mass ratio of the modified regenerated cellulose fiber, the modified cotton fiber and the modified polylactic acid fiber in the dehumidifying and antistatic cotton fiber quilt core material in S4 is 50-85:5-40:5-40.
[0015] To achieve the above-mentioned purpose, the second technical solution adopted by the present invention is: a dehumidifying and antistatic cotton fiber quilt core material, which is prepared based on a preparation method of a dehumidifying and antistatic cotton fiber quilt core material.
[0016] The present invention solves the defects existing in the background technology and has the following beneficial effects: (1) The present invention provides a method for preparing a dehumidifying and antistatic cotton fiber quilt core material, wherein regenerated cellulose fibers treated with nano-alumina powder and silk fibroin powder, cotton fibers treated with hydrogen peroxide, and polylactic acid fibers treated with titanium dioxide are stacked and laid in sequence from bottom to top to obtain a dehumidifying and antistatic cotton fiber quilt core material. Compared with the cotton fiber quilt core material in the prior art, a unidirectional charge conduction structure and a unidirectional moisture conduction structure are provided, which can enable the charge and moisture generated in the quilt core material to be transferred from bottom to top. The titanium dioxide particles on the upper side can eliminate the static charge generated in the quilt core material by redistributing the charge, and can promote the evaporation of moisture in a photocatalytic manner, thereby solving the defects of the cotton fiber quilt core material in the prior art in terms of weak dehumidification and antistatic properties during use.
[0017] (2) In the present invention, the regenerated cellulose fibers are sprayed in groups during the atomization spraying process. The silk fibroin treatment agent in each group is consistent. The grouping is based on the atomization spraying time of the silk fibroin treatment agent, so that the silk fibroin treatment agent can be evenly covered on the regenerated cellulose fibers, increasing the surface hydrophilicity of the fibers. Compared with the existing technology, a gradient structure can be formed, which drives the initial movement of moisture and charge, thereby ensuring the moisture removal and antistatic properties of the cotton fiber quilt core material.
[0018] (3) In the present invention, aluminum oxide powder exists in the modified regenerated cellulose fiber and titanium dioxide powder exists in the modified polylactic acid fiber, and they are arranged in the bottom layer and the top layer respectively, so as to form an electrostatic shielding structure. Compared with the existing technology, it can avoid the accumulation of static electricity, reduce the content of static electricity, and improve the antistatic property of the material. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the following briefly introduces the drawings required for use in the embodiments or the description of the prior art. Obviously, the drawings described below are only some embodiments described in the present invention. Those skilled in the art can also derive other drawings based on these drawings without inventive efforts. Figure 1 It is a method step diagram of a preferred embodiment of the present invention. DETAILED DESCRIPTION
[0020] The following will clearly and completely describe the technical solutions in the embodiments of the present invention in conjunction with the accompanying drawings. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative efforts are within the scope of protection of the present invention.
[0021] In the following description, many specific details are set forth to facilitate a full understanding of the present invention. However, the present invention may also be implemented in other ways different from those described herein. Therefore, the scope of protection of the present invention is not limited to the specific embodiments disclosed below.
[0022] like Figure 1 As shown, a method for preparing a dehumidifying and antistatic cotton fiber quilt core material comprises the following steps: S1: adding nano-alumina powder and silk fibroin powder to dimethyl sulfoxide, stirring to obtain a silk fibroin treatment agent, and spraying the silk fibroin treatment agent onto regenerated cellulose fibers for 1-2 hours to obtain modified regenerated cellulose fibers; S2: treating the cotton fiber with a hydrogen peroxide solution for 0.5-1 h to obtain modified cotton fiber; S3: adding nano-titanium dioxide particles to ethanol and stirring to obtain a titanium dioxide treatment agent, and immersing the polylactic acid fiber in the titanium dioxide treatment agent for 30-45 minutes to obtain a modified polylactic acid fiber; S4: The modified regenerated cellulose fiber in S1, the modified cotton fiber in S2 and the modified polylactic acid fiber in S3 are combed and layered, and the modified regenerated cellulose fiber, modified cotton fiber and modified polylactic acid fiber are arranged from bottom to top to obtain a dehumidifying and antistatic cotton fiber quilt core material.
[0023] A dehumidifying and antistatic cotton fiber quilt core material is obtained by stacking and laying regenerated cellulose fibers treated with nano-alumina powder and silk fibroin powder, cotton fibers treated with hydrogen peroxide, and polylactic acid fibers treated with titanium dioxide in sequence from bottom to top. A unidirectional charge conduction structure and a unidirectional moisture conduction structure are provided, so that the charge and moisture generated in the quilt core material can be transferred from bottom to top. The titanium dioxide particles on the upper side can eliminate the static charge generated in the quilt core material by redistributing the charge, and can promote the evaporation of moisture in a photocatalytic manner, thereby solving the defects of the cotton fiber quilt core material in the prior art in terms of weak dehumidification and antistatic properties during use.
[0024] The particle diameter of the alumina powder in S1 is 10-50nm, the particle diameter of the silk fibroin powder is 200-400nm, and the mass ratio between the alumina powder and the silk fibroin powder is 1:5-7. Nano-alumina powder has good conductivity and can be used as an antistatic material. Adding nano-alumina powder to the quilt material can improve its antistatic properties and reduce the accumulation of static electricity. Silk fibroin has certain water solubility, structural modification, good biocompatibility and biodegradability. These properties help improve the moisture removal of the material because it can absorb and release water, thereby regulating the humidity of the quilt material. Smaller alumina particles can provide more contact points, enhancing the material's conductivity and hygroscopicity.
[0025] The silk fibroin treatment agent in S1 contains 10-20% silk fibroin powder at a concentration of 4-6 denier regenerated cellulose fibers. Regenerated cellulose fibers have excellent moisture absorption and air permeability. A fineness of 4-6 denier increases the fiber's surface area, thereby improving its ability to absorb moisture and perspiration. While maintaining the fiber's softness and comfort, the natural properties of silk fibroin reduce the generation and accumulation of static electricity. These properties of silk fibroin give the treated fibers enhanced antistatic properties.
[0026] During the atomization spraying process in S1, the regenerated cellulose fibers were sprayed in groups. Each group received the same silk fibroin treatment agent, and the grouping was based on the atomization spraying time of the silk fibroin treatment agent. The spraying time of the regenerated cellulose fibers in several groups was increased from 1 hour to 2 hours, and the spraying time difference between the groups was equal. The spraying time difference was inversely proportional to the number of groups, and the number of groups was 6-8. During the layered laying process, the modified regenerated cellulose fibers in each layer were all from the same group. The spraying time of the modified regenerated cellulose fibers gradually increased from top to bottom.
[0027] Through atomized spraying, the silk fibroin treatment agent can evenly cover the regenerated cellulose fibers, increasing the fiber's surface hydrophilicity and thus improving the fiber's moisture absorption and dehumidification capabilities. Silk fibroin can increase the fiber's hygroscopicity, thereby reducing the fiber's surface resistivity, allowing charges to dissipate along the fiber surface and reducing the accumulation of static electricity.
[0028] The gradient structure design allows the distribution of silk fibroin and aluminum oxide in the material to change from the surface to the interior, which helps regulate the material's moisture absorption and moisture removal properties. Silk fibroin has good hygroscopicity and can absorb and release water, and the gradient structure can optimize this property, making the material have different water absorption and release capabilities in different areas, thereby improving the overall moisture removal properties. In the gradient structure, the change in aluminum oxide concentration can form different charge conduction paths, which helps to disperse and conduct charges, reduce the accumulation of static electricity, and the static electricity guidance process prevents the retention of static electricity in the core material.
[0029] The hydrogen peroxide solution in S2 has a concentration of 25-35%, and the cotton fiber fineness is 1-2D. The hydrogen peroxide solution removes natural pigments and impurities from the cotton fibers during the bleaching process, thereby improving the fabric's water absorption. The cotton fibers after hydrogen peroxide bleaching have a cleaner surface, reducing the accumulation of impurities and oil stains that often cause static electricity. This means that the treated cotton fibers are better able to absorb and release moisture, enhancing the moisture-wicking properties of the quilt core material.
[0030] The ethanol concentration in S3 is 95%, the nano-titanium dioxide particles have a particle diameter of 100-200nm, and the concentration of nano-titanium dioxide particles in the titanium dioxide treatment agent is 1:10-15. Nano-titanium dioxide (TiO2) is a photocatalyst that can generate photogenerated electron-hole pairs under ultraviolet light. These electron-hole pairs can decompose organic pollutants, disinfect, combat pollution, and prevent fogging. It can promote water evaporation through photocatalysis, thereby improving the moisture-wicking properties of the quilt core material. Nano-titanium dioxide has excellent electrical conductivity and can be used as an antistatic material. Adding nano-titanium dioxide to the quilt core material can improve its antistatic properties and reduce the accumulation of static electricity. Nano-titanium dioxide can photocatalytically degrade stains in the quilt core material, preventing the accumulation of static electricity.
[0031] The fineness of the polylactic acid fibers in S3 is 1-3D, and the polylactic acid has been plasma treated. Plasma treatment can increase the oxygen content on the surface of the polylactic acid fibers. The main form of the newly added oxygen is C=O, which helps to improve the moisture-wicking properties of the fibers. Plasma treatment can change the surface properties of the polylactic acid fibers, reducing their resistivity, that is, improving the antistatic properties of the fibers. After plasma treatment, the friction coefficient of the polylactic acid fibers increases significantly, while the strength and elongation change is not significant, and it does not affect the mechanical properties of the fibers. This means that the treated fibers maintain their original strength while improving their antistatic properties. After plasma treatment, the surface of the polylactic acid fibers becomes rough and produces protrusions or cracks of varying degrees. These changes will directly lead to improved friction performance and enhanced cohesion, which is beneficial to the cohesion between the fibers.
[0032] The mass ratio of modified regenerated cellulose fiber, modified cotton fiber, and modified polylactic acid fiber in the dehumidifying and antistatic cotton fiber quilt core material in S4 is 50-85:5-40:5-40. By adjusting the mass ratio, it is possible to ensure that there is sufficient regenerated cellulose fiber in the quilt core material to provide good air permeability and moisture regulation functions, thereby improving the overall moisture removal performance. Adjusting the ratio of modified cotton fiber and modified polylactic acid fiber helps to balance the overall antistatic performance of the material. After the polylactic acid fiber is treated with plasma, its surface properties are improved, further enhancing its antistatic performance.
[0033] A dehumidifying and antistatic cotton fiber quilt core material is prepared based on a preparation method of a dehumidifying and antistatic cotton fiber quilt core material.
[0034] Example 1
[0035] S1: adding nano-alumina powder and silk fibroin powder to dimethyl sulfoxide, wherein the particle diameter of the alumina powder is 40 nm, the particle diameter of the silk fibroin powder is 300 nm, and the mass ratio of the alumina powder to the silk fibroin powder is 1:6, and stirring to obtain a silk fibroin treatment agent, wherein the concentration of the silk fibroin powder in the silk fibroin treatment agent is 15%, and the fineness of the regenerated cellulose fiber is 5D, and the silk fibroin treatment agent is sprayed on the regenerated cellulose fiber for 1 hour to obtain modified regenerated cellulose fiber; During the atomization spraying process, the regenerated cellulose fibers were sprayed in groups. Each group received the same silk fibroin treatment agent, and the grouping was based on the atomization spraying time of the silk fibroin treatment agent. The spraying time of the regenerated cellulose fibers in several groups was increased from 1 hour to 2 hours, and the spraying time difference between the groups was equal and inversely proportional to the number of groups. The number of groups was 5. During the layered laying process, the modified regenerated cellulose fibers in each layer were from the same group. The spraying time of the modified regenerated cellulose fibers gradually increased from top to bottom.
[0036] S2: The cotton fibers were treated with a hydrogen peroxide solution for 0.5 h to obtain modified cotton fibers; the concentration of the hydrogen peroxide solution was 30%, and the fineness of the cotton fibers was 2D.
[0037] S3: Add nano-titanium dioxide particles to ethanol and stir to obtain a titanium dioxide treatment agent, and immerse the polylactic acid fiber in the titanium dioxide treatment agent for 30-45 minutes to obtain modified polylactic acid fiber; the ethanol concentration is 95%, the particle diameter of the nano-titanium dioxide particles is 100-200nm, the concentration of the nano-titanium dioxide particles in the titanium dioxide treatment agent is 1:10, the fineness of the polylactic acid fiber is 3D, and the polylactic acid is plasma treated. S4: The modified regenerated cellulose fiber in S1, the modified cotton fiber in S2 and the modified polylactic acid fiber in S3 are combed and layered, and the modified regenerated cellulose fiber, modified cotton fiber and modified polylactic acid fiber are arranged from bottom to top. The mass ratio of the modified regenerated cellulose fiber, modified cotton fiber and modified polylactic acid fiber in the dehumidifying and antistatic cotton fiber quilt core material is 85:10:5, and a dehumidifying and antistatic cotton fiber quilt core material is obtained.
[0038] Example 2
[0039] S1: adding nano-alumina powder and silk fibroin powder to dimethyl sulfoxide, wherein the particle diameter of the alumina powder is 40 nm, the particle diameter of the silk fibroin powder is 300 nm, and the mass ratio of the alumina powder to the silk fibroin powder is 1:6, and stirring to obtain a silk fibroin treatment agent, wherein the concentration of the silk fibroin powder in the silk fibroin treatment agent is 15%, and the fineness of the regenerated cellulose fiber is 5D, and the silk fibroin treatment agent is sprayed on the regenerated cellulose fiber for 1 hour to obtain modified regenerated cellulose fiber; During the atomization spraying process, the regenerated cellulose fibers were sprayed in groups. Each group received the same silk fibroin treatment agent, and the grouping was based on the atomization spraying time of the silk fibroin treatment agent. The spraying time of the regenerated cellulose fibers in several groups was increased from 1 hour to 2 hours, and the spraying time difference between the groups was equal. The spraying time difference was inversely proportional to the number of groups, and the number of groups was 6. During the layered laying process, the modified regenerated cellulose fibers in each layer were from the same group. The spraying time of the modified regenerated cellulose fibers gradually increased from top to bottom.
[0040] S2: The cotton fibers were treated with a hydrogen peroxide solution for 0.5 h to obtain modified cotton fibers; the concentration of the hydrogen peroxide solution was 30%, and the fineness of the cotton fibers was 2D.
[0041] S3: Add nano-titanium dioxide particles to ethanol and stir to obtain a titanium dioxide treatment agent, and immerse the polylactic acid fiber in the titanium dioxide treatment agent for 30-45 minutes to obtain modified polylactic acid fiber; the ethanol concentration is 95%, the particle diameter of the nano-titanium dioxide particles is 100-200nm, the concentration of the nano-titanium dioxide particles in the titanium dioxide treatment agent is 1:10, the fineness of the polylactic acid fiber is 3D, and the polylactic acid is plasma treated. S4: The modified regenerated cellulose fiber in S1, the modified cotton fiber in S2 and the modified polylactic acid fiber in S3 are combed and layered, and the modified regenerated cellulose fiber, modified cotton fiber and modified polylactic acid fiber are arranged from bottom to top. The mass ratio of the modified regenerated cellulose fiber, modified cotton fiber and modified polylactic acid fiber in the dehumidifying and antistatic cotton fiber quilt core material is 85:10:5, and a dehumidifying and antistatic cotton fiber quilt core material is obtained.
[0042] Example 3
[0043] S1: adding nano-alumina powder and silk fibroin powder to dimethyl sulfoxide, wherein the particle diameter of the alumina powder is 40 nm, the particle diameter of the silk fibroin powder is 300 nm, and the mass ratio of the alumina powder to the silk fibroin powder is 1:6, and stirring to obtain a silk fibroin treatment agent, wherein the concentration of the silk fibroin powder in the silk fibroin treatment agent is 15%, and the fineness of the regenerated cellulose fiber is 5D, and the silk fibroin treatment agent is sprayed on the regenerated cellulose fiber for 1 hour to obtain modified regenerated cellulose fiber; During the atomization spraying process, the regenerated cellulose fibers were sprayed in groups. Each group received the same silk fibroin treatment agent, and the grouping was based on the atomization spraying time of the silk fibroin treatment agent. The spraying time of the regenerated cellulose fibers in several groups was increased from 1 hour to 2 hours, and the spraying time difference between the groups was equal. The spraying time difference was inversely proportional to the number of groups, which was 7. During the layered laying process, the modified regenerated cellulose fibers in each layer were from the same group. The spraying time of the modified regenerated cellulose fibers gradually increased from top to bottom.
[0044] S2: The cotton fibers were treated with a hydrogen peroxide solution for 0.5 h to obtain modified cotton fibers; the concentration of the hydrogen peroxide solution was 30%, and the fineness of the cotton fibers was 2D.
[0045] S3: Add nano-titanium dioxide particles to ethanol and stir to obtain a titanium dioxide treatment agent, and immerse the polylactic acid fiber in the titanium dioxide treatment agent for 30-45 minutes to obtain modified polylactic acid fiber; the ethanol concentration is 95%, the particle diameter of the nano-titanium dioxide particles is 100-200nm, the concentration of the nano-titanium dioxide particles in the titanium dioxide treatment agent is 1:10, the fineness of the polylactic acid fiber is 3D, and the polylactic acid is plasma treated. S4: The modified regenerated cellulose fiber in S1, the modified cotton fiber in S2 and the modified polylactic acid fiber in S3 are combed and layered, and the modified regenerated cellulose fiber, modified cotton fiber and modified polylactic acid fiber are arranged from bottom to top. The mass ratio of the modified regenerated cellulose fiber, modified cotton fiber and modified polylactic acid fiber in the dehumidifying and antistatic cotton fiber quilt core material is 85:10:5, and a dehumidifying and antistatic cotton fiber quilt core material is obtained.
[0046] Example 4
[0047] S1: adding nano-alumina powder and silk fibroin powder to dimethyl sulfoxide, wherein the particle diameter of the alumina powder is 40 nm, the particle diameter of the silk fibroin powder is 300 nm, and the mass ratio of the alumina powder to the silk fibroin powder is 1:6, and stirring to obtain a silk fibroin treatment agent, wherein the concentration of the silk fibroin powder in the silk fibroin treatment agent is 15%, and the fineness of the regenerated cellulose fiber is 5D, and the silk fibroin treatment agent is sprayed on the regenerated cellulose fiber for 1 hour to obtain modified regenerated cellulose fiber; During the atomization spraying process, the regenerated cellulose fibers were sprayed in groups. Each group received the same silk fibroin treatment agent, and the grouping was based on the atomization spraying time of the silk fibroin treatment agent. The spraying time of the regenerated cellulose fibers in several groups was increased from 1 hour to 2 hours, and the spraying time difference between the groups was equal. The spraying time difference was inversely proportional to the number of groups, which was 8. During the layered laying process, the modified regenerated cellulose fibers in each layer were from the same group. The spraying time of the modified regenerated cellulose fibers gradually increased from top to bottom.
[0048] S2: The cotton fibers were treated with a hydrogen peroxide solution for 0.5 h to obtain modified cotton fibers; the concentration of the hydrogen peroxide solution was 30%, and the fineness of the cotton fibers was 2D.
[0049] S3: Add nano-titanium dioxide particles to ethanol and stir to obtain a titanium dioxide treatment agent, and immerse the polylactic acid fiber in the titanium dioxide treatment agent for 30-45 minutes to obtain modified polylactic acid fiber; the ethanol concentration is 95%, the particle diameter of the nano-titanium dioxide particles is 100-200nm, the concentration of the nano-titanium dioxide particles in the titanium dioxide treatment agent is 1:10, the fineness of the polylactic acid fiber is 3D, and the polylactic acid is plasma treated. S4: The modified regenerated cellulose fiber in S1, the modified cotton fiber in S2 and the modified polylactic acid fiber in S3 are combed and layered, and the modified regenerated cellulose fiber, modified cotton fiber and modified polylactic acid fiber are arranged from bottom to top. The mass ratio of the modified regenerated cellulose fiber, modified cotton fiber and modified polylactic acid fiber in the dehumidifying and antistatic cotton fiber quilt core material is 85:10:5, and a dehumidifying and antistatic cotton fiber quilt core material is obtained.
[0050] Example 5
[0051] S1: adding nano-alumina powder and silk fibroin powder to dimethyl sulfoxide, wherein the particle diameter of the alumina powder is 40 nm, the particle diameter of the silk fibroin powder is 300 nm, and the mass ratio of the alumina powder to the silk fibroin powder is 1:6, and stirring to obtain a silk fibroin treatment agent, wherein the concentration of the silk fibroin powder in the silk fibroin treatment agent is 15%, and the fineness of the regenerated cellulose fiber is 5D, and the silk fibroin treatment agent is sprayed on the regenerated cellulose fiber for 1 hour to obtain modified regenerated cellulose fiber; During the atomization spraying process, the regenerated cellulose fibers were sprayed in groups. Each group received the same silk fibroin treatment agent, and the grouping was based on the atomization spraying time of the silk fibroin treatment agent. The spraying time of the regenerated cellulose fibers in several groups was increased from 1 hour to 2 hours, and the spraying time difference between the groups was equal. The spraying time difference was inversely proportional to the number of groups, which was 9. During the layered laying process, the modified regenerated cellulose fibers in each layer were from the same group. The spraying time of the modified regenerated cellulose fibers gradually increased from top to bottom.
[0052] S2: The cotton fibers were treated with a hydrogen peroxide solution for 0.5 h to obtain modified cotton fibers; the concentration of the hydrogen peroxide solution was 30%, and the fineness of the cotton fibers was 2D.
[0053] S3: Add nano-titanium dioxide particles to ethanol and stir to obtain a titanium dioxide treatment agent, and immerse the polylactic acid fiber in the titanium dioxide treatment agent for 30-45 minutes to obtain modified polylactic acid fiber; the ethanol concentration is 95%, the particle diameter of the nano-titanium dioxide particles is 100-200nm, the concentration of the nano-titanium dioxide particles in the titanium dioxide treatment agent is 1:10, the fineness of the polylactic acid fiber is 3D, and the polylactic acid is plasma treated. S4: The modified regenerated cellulose fiber in S1, the modified cotton fiber in S2 and the modified polylactic acid fiber in S3 are combed and layered, and the modified regenerated cellulose fiber, modified cotton fiber and modified polylactic acid fiber are arranged from bottom to top. The mass ratio of the modified regenerated cellulose fiber, modified cotton fiber and modified polylactic acid fiber in the dehumidifying and antistatic cotton fiber quilt core material is 85:10:5, and a dehumidifying and antistatic cotton fiber quilt core material is obtained.
[0054] Example 6
[0055] S1: adding nano-alumina powder and silk fibroin powder to dimethyl sulfoxide, wherein the particle diameter of the alumina powder is 40 nm, the particle diameter of the silk fibroin powder is 300 nm, and the mass ratio of the alumina powder to the silk fibroin powder is 1:6, and stirring to obtain a silk fibroin treatment agent, wherein the concentration of the silk fibroin powder in the silk fibroin treatment agent is 15%, and the fineness of the regenerated cellulose fiber is 5D, and the silk fibroin treatment agent is sprayed on the regenerated cellulose fiber for 1 hour to obtain modified regenerated cellulose fiber; During the atomization spraying process, the regenerated cellulose fibers were sprayed in groups. Each group received the same silk fibroin treatment agent, and the grouping was based on the atomization spraying time of the silk fibroin treatment agent. The spraying time of the regenerated cellulose fibers in several groups was increased from 1 hour to 2 hours, and the spraying time difference between the groups was equal. The spraying time difference was inversely proportional to the number of groups, which was 7. During the layered laying process, the modified regenerated cellulose fibers in each layer were from the same group. The spraying time of the modified regenerated cellulose fibers gradually increased from top to bottom.
[0056] S2: The cotton fibers were treated with a hydrogen peroxide solution for 0.5 h to obtain modified cotton fibers; the concentration of the hydrogen peroxide solution was 30%, and the fineness of the cotton fibers was 2D.
[0057] S3: Add nano-titanium dioxide particles to ethanol and stir to obtain a titanium dioxide treatment agent, and immerse the polylactic acid fiber in the titanium dioxide treatment agent for 30-45 minutes to obtain modified polylactic acid fiber; the ethanol concentration is 95%, the particle diameter of the nano-titanium dioxide particles is 100-200nm, the concentration of the nano-titanium dioxide particles in the titanium dioxide treatment agent is 1:5, the fineness of the polylactic acid fiber is 3D, and the polylactic acid is plasma treated. S4: The modified regenerated cellulose fiber in S1, the modified cotton fiber in S2 and the modified polylactic acid fiber in S3 are combed and layered, and the modified regenerated cellulose fiber, modified cotton fiber and modified polylactic acid fiber are arranged from bottom to top. The mass ratio of the modified regenerated cellulose fiber, modified cotton fiber and modified polylactic acid fiber in the dehumidifying and antistatic cotton fiber quilt core material is 85:10:5, and a dehumidifying and antistatic cotton fiber quilt core material is obtained.
[0058] Example 7
[0059] S1: adding nano-alumina powder and silk fibroin powder to dimethyl sulfoxide, wherein the particle diameter of the alumina powder is 40 nm, the particle diameter of the silk fibroin powder is 300 nm, and the mass ratio of the alumina powder to the silk fibroin powder is 1:6, and stirring to obtain a silk fibroin treatment agent, wherein the concentration of the silk fibroin powder in the silk fibroin treatment agent is 15%, and the fineness of the regenerated cellulose fiber is 5D, and the silk fibroin treatment agent is sprayed on the regenerated cellulose fiber for 1 hour to obtain modified regenerated cellulose fiber; During the atomization spraying process, the regenerated cellulose fibers were sprayed in groups. Each group received the same silk fibroin treatment agent, and the grouping was based on the atomization spraying time of the silk fibroin treatment agent. The spraying time of the regenerated cellulose fibers in several groups was increased from 1 hour to 2 hours, and the spraying time difference between the groups was equal. The spraying time difference was inversely proportional to the number of groups, which was 7. During the layered laying process, the modified regenerated cellulose fibers in each layer were from the same group. The spraying time of the modified regenerated cellulose fibers gradually increased from top to bottom.
[0060] S2: The cotton fibers were treated with a hydrogen peroxide solution for 0.5 h to obtain modified cotton fibers; the concentration of the hydrogen peroxide solution was 30%, and the fineness of the cotton fibers was 2D.
[0061] S3: Add nano-titanium dioxide particles to ethanol and stir to obtain a titanium dioxide treatment agent, and immerse the polylactic acid fiber in the titanium dioxide treatment agent for 30-45 minutes to obtain modified polylactic acid fiber; the ethanol concentration is 95%, the particle diameter of the nano-titanium dioxide particles is 100-200nm, the concentration of the nano-titanium dioxide particles in the titanium dioxide treatment agent is 1:15, the fineness of the polylactic acid fiber is 3D, and the polylactic acid is treated with plasma. S4: The modified regenerated cellulose fiber in S1, the modified cotton fiber in S2 and the modified polylactic acid fiber in S3 are combed and layered, and the modified regenerated cellulose fiber, modified cotton fiber and modified polylactic acid fiber are arranged from bottom to top. The mass ratio of the modified regenerated cellulose fiber, modified cotton fiber and modified polylactic acid fiber in the dehumidifying and antistatic cotton fiber quilt core material is 85:10:5, and a dehumidifying and antistatic cotton fiber quilt core material is obtained.
[0062] Example 8
[0063] S1: adding nano-alumina powder and silk fibroin powder to dimethyl sulfoxide, wherein the particle diameter of the alumina powder is 40 nm, the particle diameter of the silk fibroin powder is 300 nm, and the mass ratio of the alumina powder to the silk fibroin powder is 1:6, and stirring to obtain a silk fibroin treatment agent, wherein the concentration of the silk fibroin powder in the silk fibroin treatment agent is 15%, and the fineness of the regenerated cellulose fiber is 5D, and the silk fibroin treatment agent is sprayed on the regenerated cellulose fiber for 1 hour to obtain modified regenerated cellulose fiber; During the atomization spraying process, the regenerated cellulose fibers were sprayed in groups. Each group received the same silk fibroin treatment agent, and the grouping was based on the atomization spraying time of the silk fibroin treatment agent. The spraying time of the regenerated cellulose fibers in several groups was increased from 1 hour to 2 hours, and the spraying time difference between the groups was equal. The spraying time difference was inversely proportional to the number of groups, which was 7. During the layered laying process, the modified regenerated cellulose fibers in each layer were from the same group. The spraying time of the modified regenerated cellulose fibers gradually increased from top to bottom.
[0064] S2: The cotton fibers were treated with a hydrogen peroxide solution for 0.5 h to obtain modified cotton fibers; the concentration of the hydrogen peroxide solution was 30%, and the fineness of the cotton fibers was 2D.
[0065] S3: Add nano-titanium dioxide particles to ethanol and stir to obtain a titanium dioxide treatment agent, and immerse the polylactic acid fiber in the titanium dioxide treatment agent for 30-45 minutes to obtain modified polylactic acid fiber; the ethanol concentration is 95%, the particle diameter of the nano-titanium dioxide particles is 100-200nm, the concentration of the nano-titanium dioxide particles in the titanium dioxide treatment agent is 1:20, the fineness of the polylactic acid fiber is 3D, and the polylactic acid is plasma treated. S4: The modified regenerated cellulose fiber in S1, the modified cotton fiber in S2 and the modified polylactic acid fiber in S3 are combed and layered, and the modified regenerated cellulose fiber, modified cotton fiber and modified polylactic acid fiber are arranged from bottom to top. The mass ratio of the modified regenerated cellulose fiber, modified cotton fiber and modified polylactic acid fiber in the dehumidifying and antistatic cotton fiber quilt core material is 85:10:5, and a dehumidifying and antistatic cotton fiber quilt core material is obtained.
[0066] Example 9
[0067] S1: adding nano-alumina powder and silk fibroin powder to dimethyl sulfoxide, wherein the particle diameter of the alumina powder is 40 nm, the particle diameter of the silk fibroin powder is 300 nm, and the mass ratio of the alumina powder to the silk fibroin powder is 1:6, and stirring to obtain a silk fibroin treatment agent, wherein the concentration of the silk fibroin powder in the silk fibroin treatment agent is 15%, and the fineness of the regenerated cellulose fiber is 5D, and the silk fibroin treatment agent is sprayed on the regenerated cellulose fiber for 1 hour to obtain modified regenerated cellulose fiber; During the atomization spraying process, the regenerated cellulose fibers were sprayed in groups. Each group received the same silk fibroin treatment agent, and the grouping was based on the atomization spraying time of the silk fibroin treatment agent. The spraying time of the regenerated cellulose fibers in several groups was increased from 1 hour to 2 hours, and the spraying time difference between the groups was equal. The spraying time difference was inversely proportional to the number of groups, which was 7. During the layered laying process, the modified regenerated cellulose fibers in each layer were from the same group. The spraying time of the modified regenerated cellulose fibers gradually increased from top to bottom.
[0068] S2: The cotton fibers were treated with a hydrogen peroxide solution for 0.5 h to obtain modified cotton fibers; the concentration of the hydrogen peroxide solution was 30%, and the fineness of the cotton fibers was 2D.
[0069] S3: Add nano-titanium dioxide particles to ethanol and stir to obtain a titanium dioxide treatment agent, and immerse the polylactic acid fiber in the titanium dioxide treatment agent for 30-45 minutes to obtain modified polylactic acid fiber; the ethanol concentration is 95%, the particle diameter of the nano-titanium dioxide particles is 100-200nm, the concentration of the nano-titanium dioxide particles in the titanium dioxide treatment agent is 1:20, the fineness of the polylactic acid fiber is 3D, and the polylactic acid is plasma treated. S4: The modified regenerated cellulose fiber in S1, the modified cotton fiber in S2 and the modified polylactic acid fiber in S3 are combed and layered, and the modified regenerated cellulose fiber, modified cotton fiber and modified polylactic acid fiber are arranged from bottom to top. The mass ratio of the modified regenerated cellulose fiber, modified cotton fiber and modified polylactic acid fiber in the dehumidifying and antistatic cotton fiber quilt core material is 85:10:5, and a dehumidifying and antistatic cotton fiber quilt core material is obtained.
[0070] The samples in Examples 1 to 9 and Comparative Example 1 were subjected to antistatic tests and moisture dissipation tests, respectively. The test results are shown in Table 1.
[0071] Table 1 Antistatic and moisture-dissipating test data of Examples 1 to 9 and Comparative Example 1
[0072] As can be seen from Table 1, the conductivity and moisture removal rate in Examples 1 to 9 are greater than those in Comparative Example 1. The preparation method of the dehumidifying and antistatic cotton fiber quilt core material in this application is superior.
[0073] In Examples 1 to 5, as the number of groups increases, the conductivity and water removal first increase and then decrease. This is because the doping level of the solid-state semiconductor will cause a large change in conductivity. Increasing the doping level will cause the conductivity to increase. For the silk fibroin treatment agent, as the spraying time increases, the amount of silk fibroin deposited on the fiber increases, thereby increasing the conductivity. The gradient trend formed by the increase in the amount of silk fibroin deposited on the fiber is larger, resulting in an increase in water removal rate. However, when the number of groups is too large, the excessive amount of silk fibroin leads to poor contact between the fibers, which in turn reduces the conductivity. The excessive amount of silk fibroin leads to excessive hygroscopicity, which weakens the water flow trend. The preferred embodiment is Example 3.
[0074] In Examples 3 and 6 to 9, as the concentration of nano-titanium dioxide particles in the titanium dioxide treatment agent gradually increases, the conductivity and moisture removal first increase and then decrease. This is because the dispersibility of the nano-titanium dioxide particles in the treatment agent has a significant impact on its conductivity and moisture removal rate. When the concentration of the nano-titanium dioxide particles is low, they are well dispersed in the matrix, which is conducive to improving the conductivity and moisture removal rate. As the concentration increases, the degree of agglomeration between the nano-titanium dioxide particles increases, which reduces their dispersibility in the matrix, thereby reducing the contact area and conductive path, resulting in a decrease in conductivity and moisture removal rate. The preferred embodiment is Example 7.
[0075] The above description is based on the ideal embodiment of the present invention. Based on the above description, relevant personnel can make various changes and modifications without departing from the technical scope of this invention. The technical scope of this invention is not limited to the content of the specification and must be determined according to the scope of the claims.
Claims
1. A method for preparing a dehumidifying antistatic cotton fiber quilt core material, characterized in that: The following steps are involved: S1: adding nano-alumina powder and silk fibroin powder to dimethyl sulfoxide, stirring to obtain a silk fibroin treatment agent, and spraying the silk fibroin treatment agent on the regenerated cellulose fiber for 1-2 hours to obtain modified regenerated cellulose fiber; S2: treating the cotton fiber with a hydrogen peroxide solution for 0.5-1 h to obtain modified cotton fiber; S3: adding nano titanium dioxide particles into ethanol, stirring to obtain a titanium dioxide treating agent, and immersing the polylactic acid fiber in the titanium dioxide treating agent for 30-45 minutes to obtain a modified polylactic acid fiber; S4: combing and layering the modified regenerated cellulose fiber in S1, the modified cotton fiber in S2 and the modified polylactic acid fiber in S3, wherein the modified regenerated cellulose fiber, the modified cotton fiber and the modified polylactic acid fiber are arranged from bottom to top to obtain a dehumidifying and antistatic cotton fiber quilt core material.
2. The method for preparing a dehumidifying and antistatic cotton fiber quilt core material according to claim 1, characterized in that: The particle diameter of the aluminum oxide powder in S1 is 10-50 nm, the particle diameter of the silk fibroin powder is 200-400 nm, and the mass ratio between the aluminum oxide powder and the silk fibroin powder is 1:5-7.
3. The method for preparing a dehumidifying and antistatic cotton fiber quilt core material according to claim 1, characterized in that: The concentration of the silk fibroin powder in the silk fibroin treating agent in S1 is 10-20%, the fineness of the regenerated cellulose fiber is 4-6D, and the regenerated cellulose fiber is one of lyocell fiber, viscose fiber and modal fiber.
4. The method for preparing a dehumidifying and antistatic cotton fiber quilt core material according to claim 3, characterized in that: During the atomization spraying process in S1, the regenerated cellulose fibers are sprayed in groups, the silk fibroin treatment agent in each group is consistent, and the grouping is based on the atomization spraying time of the silk fibroin treatment agent.
5. The method for preparing a dehumidifying and antistatic cotton fiber quilt core material according to claim 4, characterized in that: The spraying time of the regenerated cellulose fibers in several groups is increased from 1 hour to 2 hours respectively, the spraying time difference between several groups is equal, and the spraying time difference is inversely proportional to the number of groups, the number of groups is 6-8 groups, and during the layered laying process, the modified regenerated cellulose fibers in each layer are all from the same group, and the spraying time of the modified regenerated cellulose fibers gradually increases from top to bottom.
6. The method for preparing a dehumidifying and antistatic cotton fiber quilt core material according to claim 1, characterized in that: The concentration of the hydrogen peroxide solution in S2 is 25-35%, and the fineness of the cotton fiber is 1-2D.
7. The method for preparing a dehumidifying and antistatic cotton fiber quilt core material according to claim 1, characterized in that: The ethanol concentration in S3 is 95%, the particle diameter of the nano titanium dioxide particles is 100-200 nm, and the concentration of the nano titanium dioxide particles in the titanium dioxide treating agent is 1:10-15.
8. The method for preparing a dehumidifying and antistatic cotton fiber quilt core material according to claim 1, characterized in that: The fineness of the polylactic acid fiber in S3 is 1-3D, and the polylactic acid is plasma treated.
9. The method for preparing a dehumidifying and antistatic cotton fiber quilt core material according to claim 1, characterized in that: The mass ratio of the modified regenerated cellulose fiber, the modified cotton fiber and the modified polylactic acid fiber in the dehumidifying and antistatic cotton fiber quilt core material in S4 is 50-85:5-40:5-40.
10. A dehumidifying and antistatic cotton fiber quilt core material, characterized in that: It is prepared based on the preparation method of a dehumidifying and antistatic cotton fiber quilt core material described in any one of claims 1-9.